Hyperactivity and Learning Problems: Implications for Teachers. - Keogh, Barbara K. (Education Digest, 1971)
The article presents information on the hyperactivity and learning problems in children. Hyperactive children, many of whom were previously labeled as acting out, aggressive, or manifesting a behavior disturbance, have long been recognized. The chronic and disruptive nature of hyperactivity makes it easy to understand why parents and teachers are irritated by the behavior. The question of why the hyperactive child has learning problems is not so clear, however. Indeed, a number of children with remarkably high energy and activity levels are superior learners and high achievers. Often, however, the hyperactive child's fidgety, noisy behavior is associated with serious learning problems that frustrate and puzzle teachers and remedial specialists alike. In order to learn in school, a child must sit still and attend to the material being presented, and the child must sustain his attention long enough to take in the necessary information. He must also delay his response long enough to figure out the best or most reasonable answer or solution, and must organize and control his performance to produce a "correct" response.